Oxidative intercalation for monometallic Ni2+-Ni3+ layered double hydroxide and enhanced capacitance in exfoliated nanosheets - Gu, Feng (2015)
Monometallic Ni2+-Ni3+ layered double hydroxide (LDH) is prepared using a simple oxidative intercalation process and may be further exfoliated into positively charged Ni(OH)2 unilamellar sheets. The superior capacitive behavior of the unilamellar sheets stranded in carbon nanotubes (CNTs) networks is achieved because of the complete interfacial charge storage arising from the confined Faradaic reactions at the interfacial region. 3D nanosheet/CNT composites are prepared using an in situ electrostatic assembly of positive charged sheets with CNTs bearing negative charges. The restacking of active nanosheets during electrochemical cycling is effectively prohibited. Consequently, the outstanding specific capacitance and remarkable rate capability of the nanosheet/CNT hybrid electrodes are demonstrated, making them promising candidates for high performance supercapacitors, combining high-energy storage densities with high levels of power delivery.